2021
DOI: 10.1186/s12931-021-01662-7
|View full text |Cite
|
Sign up to set email alerts
|

Impulse oscillometry for detection of small airway dysfunction in subjects with chronic respiratory symptoms and preserved pulmonary function

Abstract: Background Subjects with chronic respiratory symptoms and preserved pulmonary function (PPF) may have small airway dysfunction (SAD). As the most common means to detect SAD, spirometry needs good cooperation and its reliability is controversial. Impulse oscillometry (IOS) may complete the deficiency of spirometry and have higher sensitivity. We aimed to explore the diagnostic value of IOS to detect SAD in symptomatic subjects with PPF. Methods The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…Li et al reported that among IOS parameters, AX and Fres are associated with asthma. 15 Similarly, our study revealed significant differences in Fres, X5 and AX between the two groups. X5 is defined as the peripheral elastic resistance.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Li et al reported that among IOS parameters, AX and Fres are associated with asthma. 15 Similarly, our study revealed significant differences in Fres, X5 and AX between the two groups. X5 is defined as the peripheral elastic resistance.…”
Section: Discussionsupporting
confidence: 70%
“… 32 In contrast, IOS might be a useful method for detecting SAD in subjects with chronic respiratory symptoms because of its higher sensitivity. 15 It seems that IOS has certain value in predicting BHR. Li et al reported that among IOS parameters, AX and Fres are associated with asthma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in subjects with chronic respiratory symptoms and normal spirometry, IOS was more sensitive in revealing SAD and correlated better with symptoms than spirometry. 15 In patients with COPD, IOS parameters showed a better correlation with small airway changes assessed by endo-bronchial optical coherence tomography than spirometry. 16 In asthmatic patients with normal FEV1 values, IOS revealed SAD, which was found to be associated with poor disease control and a history of asthma exacerbations.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies showed that spirometry was less sensitive in detecting both small and large airway dysfunction, as compared to IOS across a broad spectrum of clinical and research settings. 5,[14][15][16][17] In a cohort of ironworkers exposed to the catastrophic events at the World Trade Center (WTC), Skloot et al 14 showed that IOS revealed airway obstruction, expressed by abnormal R5 value, in 53% of subjects, while spirometry identified obstruction, defined by FEV1/FVC ≤ 0.70 and FEV1< 80% pred, in only 17% of subjects. Tellingly, in symptomatic individuals with WTC dust/fume exposure and normal For personal use only.…”
Section: Discussionmentioning
confidence: 99%